A fully automatic polygon scaled boundary finite element method for modelling crack propagation. (January 2015) - Dai, Shangqiu; Augarde, Charles; Du, Chengbin; Chen, Denghong
Highlights: New method for fracture analysis using SBFEM. More efficient remeshing in the SBFEM. Use of polygon SBFEs. Abstract: An automatic crack propagation remeshing procedure using the polygon scaled boundary FEM is presented. The remeshing algorithm, developed to model any arbitrary shape, is simple yet flexible because only minimal changes are made to the global mesh in each step. Fewer polygon elements are used to predict the final crack path with the algorithm as compared to previous approaches. Two simple polygon optimisation methods which enable the remeshing procedure to model crack propagation more stably are implemented. Four crack propagation benchmarks are modelled to validate the developed method and demonstrate its salient features.